Clinical experience with enteral tube nutrition and Nutrison® range of enteral tubes in patients with specific enteral feeding requirements in Spain: The NUTRECONSONDA study - M.D. Ballesteros-Pomar; J.J. Alfaro-Martínez; J.M. Guardia-Baena; M. Riestra Fernández; B. Vega-Piñero; Ana Artero Fullana; Montserrat Gonzalo Marín; Daniel De Luis Román; Ana Jiménez Portilla; Juan De Dios Barranco Ochoa; Marta Ventosa Viña; Silvia Veses Martin; et al. (Clinical Nutrition Open Science)
Summary: Background & aims: Enteral nutrition (EN) is a critical medical nutritional treatment designed to meet the specific micro- and macronutrient requirements of patients unable to achieve adequate nutrition through oral intake. The aim of this study is to review the use of EN by tube in routine clinical practice, focusing on its management in patients with specific nutritional requirements, and to evaluate the effectiveness, tolerability, and quality of life improvements associated with the Nutrison® range of enteral tube enteral formulas. Methods: NUTRECONSONDA was a nationwide, multicentre, cross-sectional ecological study. Aggregated data were collected from the experience and knowledge of 142 physicians with experience treating patients with EN through an online survey. Results: According to the physicians, the main indications to EN were neoplasms (43.3 %) and neuromotor disorders (36.4 %), the most common administration techniques were percutaneous endoscopic gastrostomy tube (35.6 %) and nasogastric tube (29.2 %), the most common type of feeding was bolus feeding (52.1 %), and most frequent symptoms were diarrhoea (29.2 %), nausea (21.7 %), regurgitation (21.4 %) and abdominal distension (21.1 %). Moreover, 82.8 % of patients reported good tolerance to enteral formulas and these were effective in 91.4 % of patients in terms of nutritional requirements. The most important criteria considered for the selection of an enteral formula of the Nutrison® range in patients with specific EN requirements were patient's energy and nutritional needs (score: 8.8), nutritional formula composition (score: 8.5) and tolerability of the formula (score: 8.3). Nutrison® enteral formulas were effective in terms of nutritional requirements in 92.5 % of patients, had good tolerability in 86.9 %, improved quality of life in 67.1 % and improved general health status in 75.1 %. Most patients were also satisfied with Nutrison® enteral formulas (87.2 %) and their delivery system (87.5 %). Furthermore, the most representative lipid profile benefits in patients treated with Nutrison® enteral formulas were a higher EPA and DHA intake (54.9 %) and a higher combination of medium chain triglycerides (45.5 %). Conclusion: The key factors influencing formula selection were patient energy requirements, formula composition, and tolerance. Enteral formulas of the Nutrison® range were effective, safe and improved quality of life and lipid profile in most of the patients with specific nutritional requirements.